(untitled) (Boletim de Geografia, 2011)
Since 1990 didactical material aimed at the teaching of basic notions of geography through Cartography in Elementary School is being researched, such that the sudents may build geographical notions and concepts through their efective participation in the process of knowledge acquisition. It was noted, for third grade students, that there was the need for some specific material related to lhe geography of their surrounding space. This gave way to the conceplion of the School Atlas of Contagem, MG, claborated with the use of traditional cartographical lechniques. In more than ten years of research new techniques have been developped and the cartographical methods were perfected. The official programs for the teaching of Geography in elementary school were changed, starting to value the learning of abilities related to lhe acquisition of specific competences. The respective roles of teacher and pupils are going through some drastic changes. The teacher motivates and guides the student in his/her process of acquisition of knowledge. In this context, the traditional geographical atlas started to be valued again. Parallel to this development of the pedagogical conceptions, the technological revolution initiated with the introduetion of computers in the school environment opened up a new research field for the elaoration of digital atlases. This research front introduces new theoretical and methodological challenges, since the atlas becomes a kind of pedagogical instrument that reaches beyond the class walls. The possibilities of linkages using hyperlinks are multiple. The public can be the most varied possible. The pedagogical practice is totally revolutionized. This paper analyses the evolution that occurred in the last decade, both. from the theoretical and methodological point of view and from the technological one: from the pencil to the Internet.